نقد الآراء حول وضع النحو العربي عند العرب - Raufi, Shah Rukh; Yaacob, Solehah@Nik Najah Fadilah; Abdul Rahman, Adam (The Scientific Institute For Advanced Training and Studies, 2018)
The research highlights some explanations on the status of Arabic grammar and its origin with the statement that Abu al-Aswad al-Duali was not the author of it. To develop the research presentation, the research discussion focuses on orientalists’ views toward Arabic language as well as the modern views among the Arabs also will be accounted. Therefore, based on consistent narratives and logical arguments by scholars indicated that there was no connection between Aristotle and Sibawayh. The statement had referred to the different concepts and terminologies usage in the both languages Arabic and Greek. The analysis which base on critical study as a method approach discovered the unbalance statements are still unable to defect the authenticity of great narrations and logical arguments of the clarity of Arabic grammar as a result of culture preservation as well as Quran understanding defense.